JEWISH SELF-DEFENSE IN SOUTH AMERICA - Rein, Raanan, 1960- author. ([S.l.])
1 online resource
Keywords: Jewish Self-Defense in South America charts the ways in which Jewish youth in Argentina and Uruguay organized self-defense groups in the wake of an anti-Semitic wave that swept the Southern Cone in the 1960s. The kidnapping of Nazi war criminal Adolf Eichmann in Buenos Aires in 1960 and his trial and execution in Israel in 1962, as well as the assassination of the Latvian war criminal Herberts Cukurs in Montevideo in 1965, provoked violent attacks by right-wing nationalist organizations against Jewish lives and property. Thousands of Jews decided to teach the anti-Semitic bullies a lesson and make it very clear that shedding Jewish blood would not go unpunished, that Jews were no longer passive victims. The central role that the State of Israel and its envoys played in organizing, instructing, and training self-defense activists highlights the special ties between Israel and the Jewish Diaspora. Based on more than 120 interviews with former activists of self-defense, ex-Mossad officers and veteran Israeli diplomats, as well as on archival research, this is a pioneering study on ethnicity and diaspora in a time of growing political violence in South America. This book is a valuable study for scholars and students researching Jewish history and Latin American history.